Robot- and computer-assisted craniotomy (CRANIO): from active systems to synergistic man-machine interaction - Vargas da Silveira Cunha Cruz, Victor Cesar; Follmann, A.; Popovic, A.; Bast, P.; Wu, T.; Heger, S.; Engelhardt, M.; Schmieder, Kirsten; Radermacher, K. (Proceedings of the Institution of Mechanical Engineers. Part H, Journal of engineering in medicine, 2010)
Computer and robot assistance in craniotomy/craniectomy procedures is intended to increase precision and efficiency of the removal of calvarial tumours, enabling the preoperative design and manufacturing of the corresponding implant. In the framework of the CRANIO project, an active robotic system was developed to automate the milling processes based on a predefined resection planning. This approach allows for a very efficient milling process, but lacks feedback of the intra-operative process to the surgeon. To better integrate the surgeon into the process, a new teleoperated synergistic architecture was designed. This enables the surgeon to realize changes during the procedure and use their human cognitive capabilities. The preoperative planning information is used as guidance for the user interacting with the system through a master—slave architecture. In this article, the CRANIO system is presented together with this new synergistic approach. Experiments have been performed to evaluate the accuracy of the system in active and synergistic modes for the bone milling procedure. The laboratory studies showed the general feasibility of the new concept for the selected medical procedure and determined the accuracy of the system. Although the integration of the surgeon partially reduces the efficiency of the milling process compared with a purely active (automatic) milling, it provides more feedback and flexibility to the user during the intra-operative procedure.
Online veröffentlicht: October 8, 2009
Gesehen am 21.07.2023